Alih Kode dan Campur Kode Para Tokoh dalam Film Tabularasa - Musyari, Fawas Al-Anfal; Juita, Novia (Persona: Kajian Bahasa dan Sastra, 2024)
This research aims to describe: first, the types of code switching in the film Tabularasa, second, the types of code mixing in the film Tabularasa, and three, the factors causing code switching and code mixing in the film Tabularasa. This type of research is qualitative research using descriptive methods. The data collected in this research was then analyzed using the following steps: (1) transcribing the conversations in the film into written language, (2) identifying the data according to the format provided, (3) classifying the data into types of code switching and mixing. code, (4) classifying the factors causing code switching and code mixing in the film Tabularasa, (5) discussing research findings, and (6) drawing conclusions from the research results. There are three findings in this research. First, the types of code switching found in the Tabularasa film are internal code switching and external code switching. In this research, the most dominant type of code switching found was internal code switching, namely switching from Indonesian to Minang or vice versa. Second, the type of code mixing found in the film Tabularasa was divided into two, namely internal and external code mixing. Of the two types of code mixing, the one most often found in this film is internal code mixing, namely code mixing between Indonesian and Minang or vice versa. The three factors causing code switching found in the film Tabularasa are, (1) the speaker and the person of the speaker, (2) the speech partner, (3) the presence of a third speaker, (4) the place and time the speech is carried out, (5) the mode of conversation, and (6) conversation topic. Meanwhile, the factors causing code mixing in the film Tabularasa are due to speaker and language factors. With the largest percentage in the form of speaker factors